2010
DOI: 10.1007/s00280-010-1337-6
|View full text |Cite
|
Sign up to set email alerts
|

Plasma pharmacokinetics and oral bioavailability of the 3,4,5,6-tetrahydrouridine (THU) prodrug, triacetyl-THU (taTHU), in mice

Abstract: Purpose Cytidine drugs, such as gemcitabine, undergo rapid catabolism and inactivation by cytidine deaminase (CD). 3,4,5,6-tetrahydrouridine (THU), a potent CD inhibitor, has been applied preclinically and clinically as a modulator of cytidine analogue metabolism. However, THU is only 20% orally bioavailable, which limits its preclinical evaluation and clinical use. Therefore, we characterized THU pharmacokinetics after the administration to mice of the more lipophilic pro-drug triacetyl-THU (taTHU). Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 23 publications
(56 reference statements)
0
17
0
Order By: Relevance
“…[22] A complementary approach would be to dampen the influence of CDA altogether, by combination therapy with a CDA inhibitor such as CDAi tetrahydrouridine. [23,24] There is an active clinical trial investigation of a newer CDA inhibitor being administered concomitantly with DAC to enhance its bioavailability, whose preliminary results appear promising. [25]…”
Section: Discussionmentioning
confidence: 99%
“…[22] A complementary approach would be to dampen the influence of CDA altogether, by combination therapy with a CDA inhibitor such as CDAi tetrahydrouridine. [23,24] There is an active clinical trial investigation of a newer CDA inhibitor being administered concomitantly with DAC to enhance its bioavailability, whose preliminary results appear promising. [25]…”
Section: Discussionmentioning
confidence: 99%
“…Tetrahydro-2'-deoxyuridine (1) [a] Also listed are the two known inhibitors tetrahydro-2'-deoxyuridine (1) and 3-deazacytidine (2), the known substrate (6), and the known inactive compound a-l-cytosine arabinoside (8), which were tested in this study as control compounds; see Table 2.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, CDA inhibitors are highly sought after as compounds to be co-administered with said drugs in order to improve their effectiveness. [6] For instance, it has been recently reported that CDA inhibition by the investigational drug zebularine enhances the antineoplastic activity of decitabine (5-aza-2′-deoxycytidine), a drug approved for the treatment of patients with myelodysplastic syndromes (MDS). [7] …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mice were obtained and handled in accordance with the Guide for the Care and Use of Laboratory Animals as previously described [13]. Adult female CD2F1 mice were administered a 20 mg/kg i.v.…”
Section: Methodsmentioning
confidence: 99%